1995
DOI: 10.1161/01.cir.91.10.2573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Enalapril Therapy on Cardiac Structure and Function in Patients With Left Ventricular Dysfunction

Abstract: These data demonstrate that enalapril attenuates progressive increases in LV dilatation and hypertrophy in patients with LV dysfunction. The results support the possibility that the favorable effects of enalapril reported in the SOLVD trials were related to inhibition of LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
1
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(211 citation statements)
references
References 34 publications
6
198
1
6
Order By: Relevance
“…12 For heart transplant recipients, baseline 2D echocardiograms of the donor heart were studied before explantation. For lung transplant recipients, the baseline echocardiogram was studied at the time of pretransplant evaluation.…”
Section: Measurements Of Left Ventricular Massmentioning
confidence: 99%
“…12 For heart transplant recipients, baseline 2D echocardiograms of the donor heart were studied before explantation. For lung transplant recipients, the baseline echocardiogram was studied at the time of pretransplant evaluation.…”
Section: Measurements Of Left Ventricular Massmentioning
confidence: 99%
“…2 However, the mechanisms of LV remodeling or of the benefit of ACE inhibition remain to be elucidated.…”
mentioning
confidence: 99%
“…The addition of an aldosterone antagonist is recommended in patients with moderate to severe HF. In the SOLVD echo substudy 94 , Enalapril significantly reduced LV volumes and mass while Carvedilol decreased LV volumes and increased LVEF in the ANZ HF Collaborative Group 95 . The Val‐HeFT echo substudy 10 showed similar changes in LV dimension and LVEF with valsartan therapy.…”
Section: Role Of Echocardiography In Therapeutic Interventionmentioning
confidence: 95%